Modified ultra-high molecular weight polyethylene fiber and modification method thereof

By chlorinating and grafting the ultra-high molecular weight polyethylene fibers, the surface chemical bonds rich in amino and hydroxyl groups are formed, which solves the problem of smooth surface of the fiber and is difficult to bind to the resin, and the application needs of high-performance composite materials are achieved.

CN119913748APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311430236.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Ultra-high molecular weight polyethylene fiber (UHMWPE) is difficult to form chemical bonds with resin due to its smooth surface and no reactive active points, which limits its application in composite materials.

Method used

By chlorinating the surface of UHMWPE fibers, chloride ion active sites are introduced, and then grafting reactions with graft monomers are carried out to form chemical bonds rich in amino and hydroxyl groups, improving the interface between the fiber and the resin.

Benefits of technology

On the basis of not damaging the mechanical properties of UHMWPE fibers, it improves its bonding strength and interface interaction performance with resins, and is suitable for high-performance composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004523415820000081
    Figure BDA0004523415820000081
  • Figure BDA0004523415820000131
    Figure BDA0004523415820000131
Patent Text Reader

Abstract

The invention provides a modified ultra-high molecular weight polyethylene fiber and a modification method thereof.The modification method comprises the steps that firstly, an ultra-high molecular weight polyethylene fiber raw material is pretreated, and then the pretreated ultra-high molecular weight polyethylene fiber and a chlorination solvent are put into a chlorination kettle to be subjected to chlorination reaction treatment, and finally, putting the chlorinated ultra-high molecular weight polyethylene fiber, a catalyst, a grafting monomer and deionized water into a grafting kettle, carrying out grafting reaction treatment, and cleaning and drying to obtain the ultra-high molecular weight polyethylene fiber. According to the modified ultra-high molecular weight polyethylene fiber and the modification method thereof provided by the invention, on the basis of not damaging the structure of the UHMWPE fiber and not reducing the mechanical property of the UHMWPE fiber, abundant amino groups and hydroxyl groups are chemically bonded on the surface of a polyethylene material, and the interface interaction between the polyethylene material and a resin material is improved, so that the modified ultra-high molecular weight polyethylene fiber is easily combined with the resin material to form a composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultra-high molecular weight polyethylene fiber modification, and in particular to a modified ultra-high molecular weight polyethylene fiber and a modification method thereof. Background Art

[0002] Ultra-high molecular weight polyethylene fiber, also known as UHMWPE fiber, has an axial orientation of more than 95%, high axial tensile strength and modulus, initial modulus of more than 100GPa, tensile strength of 2-7GPa, and energy absorption performance and wear resistance of UHMWPE fiber are better than aramid fiber, and elongation at break is also significantly higher than carbon fiber, with specific strength of about 2.6 times that of carbon fiber and 1.7 times that of aramid fiber. UHMWPE fiber has excellent properties such as ultra-high strength, low density, wear resistance, low temperature resistance, good flexibility, good electrical properties, high impact energy absorption, and resistance to strong acid and alkali chemical corrosion, and plays an important role in medical materials, navigation, aerospace and military equipment. However, the oriented UHMWPE macromolecule has a small cross-sectional area and a smooth surface. The molecular chain itself is composed of methylene and does not carry polar functional groups, so that there is no reactive active point on the fiber surface, and it cannot form chemical bonds with the resin. The surface energy is low and it is not easy to be wetted by the resin, and there is no rough surface to form mechanical meshing points, which limits its application.

[0003] UHMWPE fibers can be divided into filaments and staple fibers, of which staple fibers have a higher degree of freedom and can be evenly dispersed in various matrices, making them suitable for reinforcing skeletons of composite materials. UHMWPE chopped fibers can be used for pure spinning and blending. However, the low surface tension of UHMWPE fibers makes it difficult for chopped fibers to twist, which reduces the mechanical properties of UHMWPE fiber yarns. At the same time, its low surface tension is not conducive to its combination with resins, limiting the application of UHMWPE chopped fibers in composite materials.

[0004] In order to improve the interaction between UHMWPE fibers and between it and other materials, the surface of UHMWPE fibers needs to be polarized. At present, the main methods for polarization treatment of polymer surfaces include chemical grafting, chemical corrosion, corona and plasma. After the above surface modification, the surface roughness of the ultra-high molecular weight polyethylene fiber increases, and polar groups such as carbonyl, carboxyl, and hydroxyl are introduced on the fiber surface, thereby increasing the mechanical embedding and chemical bonding between the fiber and the resin matrix. However, these methods may damage the mechanical properties of ultra-high molecular weight polyethylene fibers, and still cannot meet the industry's demand for high-performance composite materials. Moreover, modification methods such as corona and plasma are costly, require high equipment conditions, and are difficult to industrialize, and cannot be modified on an industrial scale. Summary of the invention

[0005] The object of the present invention is to provide a modified ultra-high molecular weight polyethylene fiber and a modification method thereof, which realizes that the surface of the polyethylene material is chemically bonded with abundant amino groups and hydroxyl groups, thereby improving its interface with the resin material, without destroying the structure of the UHMWPE fiber and reducing the mechanical properties of the UHMWPE fiber.

[0006] To achieve the above object, the present invention proposes the following technical solutions:

[0007] A modification method for modified ultra-high molecular weight polyethylene fiber comprises the following preparation steps:

[0008] (1) washing and drying the ultra-high molecular weight polyethylene fiber raw material to obtain dry ultra-high molecular weight polyethylene fiber;

[0009] (2) placing the dried ultra-high molecular weight polyethylene fiber, sodium hypochlorite, hydrochloric acid, and ammonium persulfate in a weight ratio of 60:200:30:1 into a chlorination kettle, performing a chlorination reaction at 20° C.-100° C. for 20 min-120 min under photocatalysis, and obtaining a chlorinated ultra-high molecular weight polyethylene fiber after washing and drying;

[0010] (3) placing the chlorinated ultra-high molecular weight polyethylene fiber obtained in step (2) into a grafting reactor with a catalyst, a grafting monomer, and deionized water to carry out a grafting reaction, and obtaining a modified ultra-high molecular weight polyethylene fiber after washing and drying;

[0011] Wherein, the catalyst is a transition metal halide or a pyridine amine compound, the weight ratio of the catalyst to the deionized water is 1:2000, and the weight fraction of the grafting monomer is 0.2%-5%.

[0012] As a preferred technical solution of the present invention, the drying temperature in step (1) is 50°C-120°C, and the drying time is 3h-48h.

[0013] As a preferred technical solution of the present invention, the chlorination temperature in step (2) is 30°C-50°C, and the chlorination reaction time is 45min-75min.

[0014] As a preferred technical solution of the present invention, the catalyst is any one of cupric chloride, cuprous chloride, cupric bromide, cuprous bromide, terpyridine, and pentamethyldiethylenetriamine, or a mixture of more than one of them.

[0015] As a preferred technical solution of the present invention, the grafting monomer is any one of acrylamide, hydroxyethyl methacrylate, acrylate, and styrene, or a mixture of more than one of them.

[0016] As a preferred technical solution of the present invention, a first xenon lamp device and a first ultrasonic generator are provided in the chlorination kettle;

[0017] The wavelength of the xenon lamp light source of the first xenon lamp device is 380nm-780nm, and the first xenon lamp device provides the light source required for photocatalysis for the chlorination reaction;

[0018] The ultrasonic frequency of the first ultrasonic generator is no higher than 80 Hz. The ultrasonic wave emitted by the first ultrasonic generator is used to provide sufficient energy for the chlorination reaction, so that the chemical bonds in the reaction substances involved in the chlorination reaction are broken to form active substances such as free radicals, which is beneficial to the bonding of ultra-high molecular weight polyethylene fibers with chloride ions.

[0019] As a preferred technical solution of the present invention, the wavelength of the xenon lamp light source of the first xenon lamp device is 400nm-500nm, and the ultrasonic frequency of the first ultrasonic generator is 45Hz-65Hz.

[0020] As a preferred technical solution of the present invention, a second xenon lamp device and a second ultrasonic generator are provided in the grafting kettle;

[0021] The wavelength of the xenon lamp light source of the second xenon lamp device is 380nm-780nm, and the second xenon lamp device provides the light source required for photocatalysis for the grafting reaction;

[0022] The ultrasonic frequency of the second ultrasonic generator is no higher than 80 Hz. The ultrasonic waves emitted by the second ultrasonic generator are used to provide sufficient energy for the grafting reaction, so that the chemical bonds in the reaction substances involved in the grafting reaction are broken to form active substances such as free radicals, which are beneficial to the bonding of the chlorinated ultra-high molecular weight polyethylene fiber and the grafting monomer.

[0023] As a preferred technical solution of the present invention, the wavelength of the xenon lamp light source of the second xenon lamp device is 400nm-500nm, and the ultrasonic frequency of the second ultrasonic generator is 45Hz-65Hz.

[0024] The present invention also provides a modified ultra-high molecular weight polyethylene fiber, which is prepared by the above-mentioned modification method.

[0025] It can be seen from the above technical scheme that the modified ultra-high molecular weight polyethylene fiber and its modification method provided by the technical scheme of the present invention adopt an intermittent production process. First, the ultra-high molecular weight polyethylene fiber is chlorinated so that it has a highly active chloride ion active site, and then it is grafted with a grafting monomer to perform surface functionalization modification on the ultra-high molecular weight polyethylene fiber. The chlorination reaction and the grafting reaction are both new technologies based on the photocatalytic ATRP reaction. The light source causes the catalyst to absorb light energy to generate electron and hole pairs with a long life, which is beneficial to the reaction substances to undergo chemical reactions on the catalyst surface. Thus, without destroying the structure of the ultra-high molecular weight polyethylene fiber and reducing the mechanical properties of the ultra-high molecular weight polyethylene fiber, a modified ultra-high molecular weight polyethylene fiber is obtained. The fiber surface is chemically bonded with rich amino groups and hydroxyls, thereby improving its interface with the resin-based material and making it easy to combine with the resin, thereby replacing carbon fiber and aramid fiber in the application field of composite materials, forming a characteristic industry of ultra-high molecular weight polyethylene fiber-enhanced composite materials in my country, promoting industrial upgrading, increasing the added value of products, and meeting the industry's demand for high-performance composite materials.

[0026] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered to be part of the inventive subject matter of the present disclosure, provided such concepts are not mutually inconsistent. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be understood by people with ordinary skills in the field to which the present invention belongs.

[0028] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular form of "a", "an" or "the" and similar words do not indicate a quantity limitation, but indicate the existence of at least one. Words such as "include" or "comprise" mean that the elements or objects appearing before "include" or "comprise" include the features, wholes, steps, operations, elements and / or components listed after "include" or "comprise", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0029] The embodiment of the present invention provides a modification method of modified ultra-high molecular weight polyethylene fiber, comprising the following preparation steps:

[0030] (1) A certain amount of ultra-high molecular weight polyethylene fiber raw material is placed in deionized water for cleaning, and then placed in an oven for drying at a drying temperature of 50°C-120°C for 3h-48h to obtain dried ultra-high molecular weight polyethylene fiber. In the embodiment of the present invention, the ultra-high molecular weight polyethylene fiber raw material can be short fibers or long fibers, i.e., ultra-high molecular weight polyethylene fibers of all lengths, wherein the preferred drying temperature is 60°C-70°C, and the preferred drying time is 5h-8h.

[0031] (2) The dried ultra-high molecular weight polyethylene fiber, sodium hypochlorite, hydrochloric acid, and ammonium persulfate are placed in a chlorination kettle in a weight ratio of 60:200:30:1, reacted at a chlorination temperature of 20°C-100°C for 20min-120min under photocatalysis, and the chlorinated ultra-high molecular weight polyethylene fiber is obtained after washing and drying. Among them, in the embodiment of the present invention, the preferred chlorination temperature is 30°C-50°C, and the preferred chlorination reaction time is 45min-75min. By chlorinating the ultra-high molecular weight polyethylene fiber, it has a relatively active chloride ion active site, so that it is easy to connect the grafted monomer to the chloride ion, which is equivalent to connecting the ultra-high molecular weight polyethylene fiber with the grafted monomer through the role of the chloride ion as an intermediate bridge.

[0032] (3) The chlorinated ultra-high molecular weight polyethylene fiber obtained in step (2) is placed in a grafting reactor with a catalyst, a grafting monomer, and deionized water to carry out a grafting reaction under photocatalysis, and the modified ultra-high molecular weight polyethylene fiber is obtained after washing and drying. The grafting monomer is connected to the other end of the chloride ion instead of being directly connected to the ultra-high molecular weight polyethylene fiber, because the chloride ion has a higher chemical activity than the group on the surface of the ultra-high molecular weight polyethylene fiber and is easier to bond with other active grafting monomers.

[0033] Wherein, the catalyst is a transition metal halide or a pyridine amine compound, the weight ratio of the catalyst to the deionized water is 1:2000, and the weight fraction of the grafting monomer is 0.2%-5%.

[0034] In the embodiment of the present invention, the catalyst is preferably any one of cupric chloride, cuprous chloride, cupric bromide, cuprous bromide, terpyridine, pentamethyldiethylenetriamine or a mixture thereof. The grafting monomer is any one of acrylamide, hydroxyethyl methacrylate, acrylate, styrene or a mixture thereof.

[0035] In an embodiment of the present invention, the chlorination kettle achieves a sufficient chlorination reaction of the ultra-high molecular weight polyethylene fiber by stirring, ultrasound, and mechanical circulation. Specifically, the chlorination kettle is provided with a first xenon lamp device, a first heating cavity, a first stirring paddle, and a first ultrasonic generator with a frequency conversion setting at its bottom. Among them, the wavelength of the xenon lamp light source of the first xenon lamp device is 380nm-780nm, preferably 400nm-500nm, which is used to provide the light source required for photocatalysis for the chlorination reaction; the first heating cavity is used to heat the material inside the chlorination kettle so that the material is maintained in a suitable reaction temperature range; the first stirring paddle is used to stir the material so that it can fully undergo a chlorination reaction. The ultrasonic frequency of the first ultrasonic generator is not higher than 80Hz, preferably 45Hz-65Hz. The ultrasonic wave emitted by the first ultrasonic generator is used to provide sufficient energy for the chlorination reaction, so that the chemical bonds in the reaction substances involved in the chlorination reaction are broken, and active substances such as free radicals are formed, which are conducive to the bonding of the ultra-high molecular weight polyethylene fiber with chloride ions, so that the material can fully undergo a chlorination reaction, and as many chloride ions as possible are bonded to the surface of the ultra-high molecular weight polyethylene fiber. A first insulation jacket and a first electric heating tape are provided on the outer wall of the chlorination kettle, wherein the first insulation jacket is filled with heat transfer oil, and the first electric heating tape is used to heat the heat transfer oil in the first insulation jacket to insulate the chlorination kettle so as to maintain the temperature of the material inside the kettle within an appropriate range.

[0036] In an embodiment of the present invention, the grafting kettle also uses stirring, ultrasound, and mechanical circulation to allow the chlorinated ultra-high molecular weight polyethylene fiber to undergo sufficient grafting reaction. Specifically, a second xenon lamp device, a second heating cavity, and a second stirring paddle are provided inside the grafting kettle, and a second ultrasonic generator with a variable frequency setting is provided at the bottom thereof, wherein the wavelength of the xenon lamp light source of the second xenon lamp device is 380nm-780nm, preferably 400nm-500nm, which is used to provide the light source required for photocatalysis for the grafting reaction; the second heating cavity is used to heat the material inside the grafting kettle to maintain the material within a suitable reaction temperature range; the second stirring paddle is used to stir the material inside the grafting kettle to allow the material to undergo sufficient grafting reaction. The ultrasonic frequency of the second ultrasonic generator is not higher than 80Hz, preferably 45Hz-65Hz. The ultrasonic wave emitted by the second ultrasonic generator provides sufficient energy for the grafting reaction, so that the chemical bonds in the reaction substances involved in the grafting reaction are broken, and active substances such as free radicals are formed, which are beneficial to the bonding of the ultra-high molecular weight polyethylene fiber and the grafting monomer, so that the material can fully undergo the grafting reaction, and the surface of the ultra-high molecular weight polyethylene fiber is bonded with as many grafting monomers as possible, thereby increasing the grafting amount. A second insulation jacket and a second electric heating belt are provided on the outer wall of the grafting kettle, wherein the second insulation jacket is filled with heat transfer oil, and the second electric heating belt is used to heat the heat transfer oil in the second insulation jacket, and to keep the chlorination kettle warm, so that the temperature of the material inside it is maintained within a suitable range.

[0037] The present invention also provides a modified ultra-high molecular weight polyethylene fiber, which is prepared by the above-mentioned modification method.

[0038] The embodiment of the present invention adopts an intermittent production process, first chlorinating the ultra-high molecular weight polyethylene fiber so that it has a highly active chloride ion active site, and then grafting it with a grafting monomer, using chloride ions as a bridge between the ultra-high molecular weight polyethylene fiber and the grafting monomer, and performing surface functionalization modification on the ultra-high molecular weight polyethylene fiber. In addition, the new technology of photocatalytic ATRP reaction is applied to the chlorination reaction and the grafting reaction, and the light source is used to cause the catalyst to absorb light energy to generate electron and hole pairs with a long life, which is conducive to the chemical reaction of the reactant on the catalyst surface, thereby obtaining a modified ultra-high molecular weight polyethylene fiber without destroying the structure of the ultra-high molecular weight polyethylene fiber and reducing the mechanical properties of the ultra-high molecular weight polyethylene fiber. The fiber surface is chemically bonded with abundant amino groups and hydroxyl groups, thereby improving its interface with the resin-based material and making it easy to combine with the resin.

[0039] The technical solution of the present invention is described below in conjunction with specific embodiments.

[0040] Example 1

[0041] (1) washing 3.0 parts by weight of an ultra-high molecular weight polyethylene fiber raw material in deionized water, drying the fiber in an oven at 60° C. to 70° C. for 7 hours, and then taking the fiber out to obtain a dried ultra-high molecular weight polyethylene fiber;

[0042] (2) adding the dried ultra-high molecular weight polyethylene fiber, 10 parts by weight of sodium hypochlorite, 1.5 parts by weight of hydrochloric acid, and 3.0 parts by weight of ammonium persulfate into a chlorination kettle from a feed port, reacting at 30° C.-50° C. for 50 minutes, and washing and drying to obtain the chlorinated ultra-high molecular weight polyethylene fiber;

[0043] (3) The chlorinated ultra-high molecular weight polyethylene fiber, 0.2 parts by weight of acrylamide, and 0.05 parts by weight of copper bromide are fed into a grafting kettle from a feed port, and after the amount of deionized water is supplemented according to the weight ratio of the catalyst to the deionized water, the grafting reaction is carried out for 50 minutes, and after washing and drying, the modified ultra-high molecular weight polyethylene fiber is obtained, which is then packaged.

[0044] (4) The surface tension and interfacial shear strength of the modified ultra-high molecular weight polyethylene fiber were tested. The test results are shown in Table 1.

[0045] Among them, the test method of the surface tension of the modified ultra-high molecular weight polyethylene fiber in the embodiment of the present invention is as follows:

[0046] Insert the modified ultra-high molecular weight polyethylene fiber mass prepared in the embodiment into a test tube with a porous bottom, and tighten the screws to compress the fiber mass to a certain height. Then hang the test tube on the contact angle meter, and lift the lifting platform of the beaker containing the test liquid to a position 2mm from the bottom of the test tube. Set the test program and run it automatically. Select three liquids with different surface tensions as test liquids, and test the same group of fibers (3 groups in total) in the above experiment. In the embodiment of the present invention, n-hexane, N,N-dimethylpropyleneamine, and dimethyl sulfoxide are selected as test liquids.

[0047] The test method for the interfacial shear strength of modified ultra-high molecular weight polyethylene fibers is as follows:

[0048] The bonding strength between the ultra-high molecular weight polyethylene fiber and the epoxy resin matrix before and after modification was measured by pulling out the single filament. First, epoxy resin E44 and curing agent 593 were prepared in a mass ratio of 100:22, and centrifuged to remove bubbles after mechanical stirring for 5 minutes. The mixed epoxy resin was poured into a mold to prepare a single filament pull-out specimen with a thickness of 1mm and an embezzlement depth of about 2mm. The test was carried out using a universal testing machine with a gauge length of 2mm and a test speed of 2mm / min, and the maximum force F was recorded. max Among them, the calculation formula of interface shear strength (IFSS) is as follows:

[0049]

[0050] Among them, F max is the maximum pull-out force of the modified ultra-high molecular weight polyethylene fiber, N is the number of fibers, D is the diameter of the modified ultra-high molecular weight polyethylene fiber (unit: m), and L is the embedding depth (unit: m).

[0051] Example 2

[0052] (1) washing 3.0 parts by weight of an ultra-high molecular weight polyethylene fiber raw material in deionized water, drying the fiber in an oven at 60° C. to 70° C. for 7 hours, and then taking the fiber out to obtain a dried ultra-high molecular weight polyethylene fiber;

[0053] (2) adding the dried ultra-high molecular weight polyethylene fiber, 10 parts by weight of sodium hypochlorite, 1.5 parts by weight of hydrochloric acid, and 3.0 parts by weight of ammonium persulfate into a chlorination kettle from a feed port, reacting at 30° C.-50° C. for 50 minutes, and washing and drying to obtain the chlorinated ultra-high molecular weight polyethylene fiber;

[0054] (3) The chlorinated ultra-high molecular weight polyethylene fiber, 0.6 parts by weight of acrylamide, and 0.05 parts by weight of copper bromide are fed into a grafting reactor from a feed port, and after the amount of deionized water is supplemented according to the weight ratio of the catalyst to the deionized water, the grafting reaction is carried out for 50 minutes, and after washing and drying, the modified ultra-high molecular weight polyethylene fiber is obtained, which is then packaged.

[0055] (4) The modified ultra-high molecular weight polyethylene fiber was tested according to the surface tension and interfacial shear strength test methods in Example 1. The test results are shown in Table 1.

[0056] Example 3

[0057] (1) washing 3.0 parts by weight of an ultra-high molecular weight polyethylene fiber raw material in deionized water, drying the fiber in an oven at 60° C. to 70° C. for 7 hours, and then taking the fiber out to obtain a dried ultra-high molecular weight polyethylene fiber;

[0058] (2) adding the dried ultra-high molecular weight polyethylene fiber, 10 parts by weight of sodium hypochlorite, 1.5 parts by weight of hydrochloric acid, and 3.0 parts by weight of ammonium persulfate into a chlorination kettle from a feed port, reacting at 30° C.-50° C. for 50 minutes, and washing and drying to obtain the chlorinated ultra-high molecular weight polyethylene fiber;

[0059] (3) The chlorinated ultra-high molecular weight polyethylene fiber, 1.0 weight part of acrylamide, and 0.05 weight part of copper bromide are fed into a grafting kettle from a feed port, and after the amount of deionized water is supplemented according to the weight ratio of the catalyst to the deionized water, the grafting reaction is carried out for 50 minutes, and after washing and drying, the modified ultra-high molecular weight polyethylene fiber is obtained, which is then packaged.

[0060] (4) The modified ultra-high molecular weight polyethylene fiber was tested according to the surface tension and interfacial shear strength test methods in Example 1. The test results are shown in Table 1.

[0061] Example 4

[0062] (1) washing 3.0 parts by weight of an ultra-high molecular weight polyethylene fiber raw material in deionized water, drying the fiber in an oven at 60° C. to 70° C. for 7 hours, and then taking the fiber out to obtain a dried ultra-high molecular weight polyethylene fiber;

[0063] (2) adding the dried ultra-high molecular weight polyethylene fiber, 10 parts by weight of sodium hypochlorite, 1.5 parts by weight of hydrochloric acid, and 3.0 parts by weight of ammonium persulfate into a chlorination kettle from a feed port, reacting at 30° C.-50° C. for 50 minutes, and washing and drying to obtain the chlorinated ultra-high molecular weight polyethylene fiber;

[0064] (3) The chlorinated ultra-high molecular weight polyethylene fiber, 1.5 parts by weight of acrylamide, and 0.05 parts by weight of copper bromide are fed into a grafting kettle from a feed port, and after the amount of deionized water is supplemented according to the weight ratio of the catalyst to the deionized water, the grafting reaction is carried out for 50 minutes, and after washing and drying, the modified ultra-high molecular weight polyethylene fiber is obtained, which is then packaged.

[0065] (4) The modified ultra-high molecular weight polyethylene fiber was tested according to the surface tension and interfacial shear strength test methods in Example 1. The test results are shown in Table 1.

[0066] Example 5

[0067] (1) washing 3.0 parts by weight of an ultra-high molecular weight polyethylene fiber raw material in deionized water, drying the fiber in an oven at 60° C. to 70° C. for 7 hours, and then taking the fiber out to obtain a dried ultra-high molecular weight polyethylene fiber;

[0068] (2) adding the dried ultra-high molecular weight polyethylene fiber, 10 parts by weight of sodium hypochlorite, 1.5 parts by weight of hydrochloric acid, and 3.0 parts by weight of ammonium persulfate into a chlorination kettle from a feed port, reacting at 30° C.-50° C. for 50 minutes, and washing and drying to obtain the chlorinated ultra-high molecular weight polyethylene fiber;

[0069] (3) The chlorinated ultra-high molecular weight polyethylene fiber, 2.0 parts by weight of acrylamide, and 0.05 parts by weight of copper bromide are fed into a grafting reactor from a feed port, and after replenishing the amount of deionized water according to the weight ratio of the catalyst to the deionized water, the grafting reaction is carried out for 50 minutes, and after washing and drying, the modified ultra-high molecular weight polyethylene fiber is obtained, which is then packaged.

[0070] (4) The modified ultra-high molecular weight polyethylene fiber was tested according to the surface tension and interfacial shear strength test methods in Example 1. The test results are shown in Table 1.

[0071] Example 6

[0072] (1) washing 3.0 parts by weight of an ultra-high molecular weight polyethylene fiber raw material in deionized water, drying the fiber in an oven at 60° C. to 70° C. for 7 hours, and then taking the fiber out to obtain a dried ultra-high molecular weight polyethylene fiber;

[0073] (2) adding the dried ultra-high molecular weight polyethylene fiber, 10 parts by weight of sodium hypochlorite, 1.5 parts by weight of hydrochloric acid, and 3.0 parts by weight of ammonium persulfate into a chlorination kettle from a feed port, reacting at 30° C.-50° C. for 50 minutes, and washing and drying to obtain the chlorinated ultra-high molecular weight polyethylene fiber;

[0074] (3) The chlorinated ultra-high molecular weight polyethylene fiber, 3.0 parts by weight of acrylamide, and 0.05 parts by weight of copper bromide are fed into a grafting reactor from a feed port, and after the amount of deionized water is supplemented according to the weight ratio of the catalyst to the deionized water, the grafting reaction is carried out for 50 minutes, and after washing and drying, the modified ultra-high molecular weight polyethylene fiber is obtained, which is then packaged.

[0075] (4) The modified ultra-high molecular weight polyethylene fiber was tested according to the surface tension and interfacial shear strength test methods in Example 1. The test results are shown in Table 1.

[0076] Example 7

[0077] (1) washing 3.0 parts by weight of an ultra-high molecular weight polyethylene fiber raw material in deionized water, drying the fiber in an oven at 60° C. to 70° C. for 7 hours, and then taking the fiber out to obtain a dried ultra-high molecular weight polyethylene fiber;

[0078] (2) adding the dried ultra-high molecular weight polyethylene fiber, 10 parts by weight of sodium hypochlorite, 1.5 parts by weight of hydrochloric acid, and 3.0 parts by weight of ammonium persulfate into a chlorination kettle from a feed port, reacting at 30° C.-50° C. for 50 minutes, and washing and drying to obtain the chlorinated ultra-high molecular weight polyethylene fiber;

[0079] (3) The chlorinated ultra-high molecular weight polyethylene fiber, 4.0 parts by weight of acrylamide, and 0.05 parts by weight of copper bromide are fed into a grafting kettle from a feed port, and after the amount of deionized water is supplemented according to the weight ratio of the catalyst to the deionized water, the grafting reaction is carried out for 50 minutes, and after washing and drying, the modified ultra-high molecular weight polyethylene fiber is obtained, which is then packaged.

[0080] (4) The modified ultra-high molecular weight polyethylene fiber was tested according to the surface tension and interfacial shear strength test methods in Example 1. The test results are shown in Table 1.

[0081] Comparative Example 1

[0082] (1) washing 3.0 parts by weight of an ultra-high molecular weight polyethylene fiber raw material in deionized water, drying the fiber in an oven at 60° C. to 70° C. for 7 hours, and then taking the fiber out to obtain a dried ultra-high molecular weight polyethylene fiber;

[0083] (2) The dried ultra-high molecular weight polyethylene fiber, 0.6 parts by weight of acrylamide, and 0.05 parts by weight of copper bromide were fed into a grafting reactor from a feed port, and the grafting reaction was carried out for 50 minutes. After washing and drying, the modified ultra-high molecular weight polyethylene fiber was obtained.

[0084] (3) The modified ultra-high molecular weight polyethylene fiber was tested according to the surface tension and interfacial shear strength test methods in Example 1. The test results are shown in Table 1.

[0085] The difference between Comparative Example 1 and Example 2 is that, in Comparative Example 1, no chlorination reaction is performed before the grafting reaction, but the ultra-high molecular weight polyethylene fiber is directly grafted with the grafting monomer. The results show that the grafting amount of Comparative Example 1 cannot be obtained due to the low value, the surface tension is 28.36 mN / m, and the interfacial shear strength cannot obtain accurate data because the fiber surface is too smooth and easy to slip. Compared with Example 2, the grafting amount is 0.10 mol / L, the surface tension is 38.15 mN / m, and the interfacial shear strength is 1.75 MPa, which shows that the ultra-high molecular weight polyethylene fiber has not been chlorinated in advance, resulting in very few active bonds on the surface of the ultra-high molecular weight polyethylene fiber, so that when the grafting reaction is carried out, the chemical bonds that the grafting monomer can bond are also very few, which ultimately leads to the ultra-high molecular weight polyethylene fiber. The grafting amount is extremely low and even cannot be measured; at the same time, it can be seen from its lowest surface tension and the interfacial shear strength that the surface of the ultra-high molecular weight polyethylene fiber is still extremely smooth, and the desired roughness improvement is not obtained, which also shows that the grafting monomer cannot or is extremely difficult to directly bond with the ultra-high molecular weight polyethylene fiber. Therefore, the modification effect of directly grafting the ultra-high molecular weight polyethylene fiber is extremely poor, and the desired modification effect cannot be obtained.

[0086] Comparative Example 2

[0087] (1) washing 3.0 parts by weight of an ultra-high molecular weight polyethylene fiber raw material in deionized water, drying the fiber in an oven at 60° C. to 70° C. for 7 hours, and then taking the fiber out to obtain a dried ultra-high molecular weight polyethylene fiber;

[0088] (2) adding the dried ultra-high molecular weight polyethylene fiber, 10 parts by weight of sodium hypochlorite, 1.5 parts by weight of hydrochloric acid, and 3.0 parts by weight of ammonium persulfate into a chlorination kettle from a feed port, reacting at 30° C.-50° C. for 50 minutes, and washing and drying to obtain the chlorinated ultra-high molecular weight polyethylene fiber;

[0089] (3) The chlorinated ultra-high molecular weight polyethylene fiber and 0.05 parts by weight of copper bromide were fed into a grafting reactor from a feed port, and the grafting reaction was carried out for 50 minutes. After washing and drying, the modified ultra-high molecular weight polyethylene fiber was obtained.

[0090] (4) The modified ultra-high molecular weight polyethylene fiber was tested according to the surface tension and interfacial shear strength test methods in Example 1. The test results are shown in Table 1.

[0091] The difference between Comparative Example 1 and Examples 1-7 is that no grafting monomer is added for grafting, so its grafting amount is 0, the surface tension is also poor, which is 35.77 mN / m, and the interfacial shear strength is the lowest, indicating that the surface tension and interfacial shear strength of the ultra-high molecular weight polyethylene fiber that has not been grafted are not as good as those after grafting modification.

[0092] Table 1 Analysis of surface tension and interfacial shear strength test data of modified ultra-high molecular weight polyethylene fibers

[0093]

[0094] It can be seen from the grafting amount of Examples 1-5 that the larger the grafting amount, the better the surface tension and interfacial shear strength performance; it can be seen from Examples 5-7 that when the grafting amount reaches a certain range, the surface tension and interfacial shear strength performance do not increase as much as before by increasing the grafting amount. Therefore, in actual production, the appropriate ratio of fiber raw material to grafting monomer can be selected as needed to achieve the optimal reaction process conditions and avoid waste of reactant raw materials. It can be seen from the experimental data results of the embodiments and comparative examples that the modified ultra-high molecular weight polyethylene fiber prepared by the modification method described in the embodiments of the present invention has very superior surface tension and interfacial shear strength, and can be efficiently compounded with other resins in the future to achieve more and better applications.

[0095] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A method for modifying ultra-high molecular weight polyethylene fiber, characterized in that: The method comprises the following preparation steps: (1) washing and drying the ultra-high molecular weight polyethylene fiber raw material to obtain dry ultra-high molecular weight polyethylene fiber; (2) placing the dried ultra-high molecular weight polyethylene fiber, sodium hypochlorite, hydrochloric acid, and ammonium persulfate in a weight ratio of 60:200:30:1 into a chlorination kettle, performing a chlorination reaction at 20° C.-100° C. for 20 min-120 min under photocatalysis, and obtaining a chlorinated ultra-high molecular weight polyethylene fiber after washing and drying; (3) placing the chlorinated ultra-high molecular weight polyethylene fiber obtained in step (2) into a grafting reactor with a catalyst, a grafting monomer, and deionized water, performing a grafting reaction under photocatalysis, and obtaining a modified ultra-high molecular weight polyethylene fiber after washing and drying; Wherein, the catalyst is a transition metal halide or a pyridine amine compound, the weight ratio of the catalyst to the deionized water is 1:2000, and the weight fraction of the grafting monomer is 0.2%-5%.

2. The method for modifying the modified ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: In the step (1), the drying temperature is 50° C.-120° C., and the drying time is 3 h-48 h.

3. The modification method of modified ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The chlorination temperature in step (2) is 30° C.-50° C., and the chlorination reaction time is 45 min-75 min.

4. The modification method of modified ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The catalyst is any one of cupric chloride, cuprous chloride, cupric bromide, cuprous bromide, terpyridine, pentamethyldiethylenetriamine or a mixture of more than one of the above.

5. The modification method of modified ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The grafting monomer is any one of acrylamide, hydroxyethyl methacrylate, acrylate, and styrene, or a mixture of more than one of them.

6. The modification method of modified ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The chlorination kettle is provided with a first xenon lamp device and a first ultrasonic generator; The wavelength of the xenon lamp light source of the first xenon lamp device is 380nm-780nm, and the first xenon lamp device provides the light source required for photocatalysis for the chlorination reaction; The ultrasonic frequency of the first ultrasonic generator is no higher than 80 Hz. The ultrasonic wave emitted by the first ultrasonic generator is used to provide energy for the chlorination reaction, so that the chemical bonds in the reaction substances are broken to form active chemical bonds.

7. The method for modifying modified ultra-high molecular weight polyethylene fiber according to claim 6, characterized in that: The wavelength of the xenon lamp light source of the first xenon lamp device is 400nm-500nm, and the ultrasonic frequency of the first ultrasonic generator is 45Hz-65Hz.

8. The modification method of modified ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The grafting kettle is provided with a second xenon lamp device and a second ultrasonic generator; The wavelength of the xenon lamp light source of the second xenon lamp device is 380nm-780nm, and the second xenon lamp device provides the light source required for photocatalysis for the grafting reaction; The ultrasonic frequency of the second ultrasonic generator is not higher than 80 Hz. The ultrasonic waves emitted by the second ultrasonic generator are used to provide energy for the grafting reaction, so that the chemical bonds in the reaction substances are broken to form active chemical bonds.

9. The method for modifying modified ultra-high molecular weight polyethylene fiber according to claim 8, characterized in that: The wavelength of the xenon lamp light source of the second xenon lamp device is 400nm-500nm, and the ultrasonic frequency of the second ultrasonic generator is 45Hz-65Hz.

10. A modified ultra-high molecular weight polyethylene fiber, characterized in that: The modified ultra-high molecular weight polyethylene fiber is obtained by the modification method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for surface functionalization treatment of UHMWPEF (Ultra High Molecular Weight Polyethylene Fiber)

    CN106120300A

  • Surface modification method for polyolefin material

    CN109679129A

  • Modification method for plant fiber or nanocellulose

    CN109810255A

  • Modified chlorinated polyethylene fiber, radome material containing modified chlorinated polyethylene fiber and preparation method of radome material

    CN116145426A

  • Fiber-reinforced resin molded body and its manufacture

    JP1988296928A